Entrepreneurial Management as an Effort to Develop the Economic Sustainability of Darul Falah Islamic Boarding School - Hamiyah Hamiyah; Ahmad Fauzan; Yosep Aspat Alamsyah (International Conference on Islamic Economic (ICIE), 2026)
This study aims to analyze entrepreneurial management as an effort to develop the economic independence of Islamic boarding schools (pesantren) through the role of LAZISWA (Institution for Zakat, Infaq, and Sadaqah Management). The background of this research is based on the importance of economic self-reliance in supporting the sustainability of Islamic-based educational institutions. In this context, entrepreneurship becomes an effective strategy, particularly when it is managed systematically and supported by internal funding sources such as LAZISWA. This study employs a qualitative approach with a descriptive method. Data collection techniques include interviews, observations, and documentation. The collected data are then analyzed using qualitative data analysis techniques, which consist of data reduction, data presentation, and conclusion drawing. The results of the study indicate that entrepreneurial management in the pesantren has been implemented systematically through the application of integrated management functions in managing various business units. The presence of LAZISWA plays a significant role as a source of productive funding that supports the development and sustainability of these business units. The synergy between entrepreneurial management and the utilization of LAZISWA funds has encouraged the establishment of various productive enterprises, contributing to the economic independence of the pesantren, improving the welfare of its community members, and strengthening the entrepreneurial spirit among the students